Health Informatics Master Program at King Saud bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia - Altwaijiri, M.; Aldosari, B. (Yearbook of Medical Informatics, 2008)
Objective The purpose of this paper is to describe the Health Informatics Master Program at King Saud bin Abdulaziz University for Health Sciences (KSAU-HS), Riyadh, Saudi Arabia.Methods We have reviewed health informatics master programs worldwide with more emphasis on the recommendations of the International Medical Informatics Association on education in health informatics, research, and faculty/trainee participation at KSAU-HS.Results An applied health informatics master program has been designed where graduates will be able to deploy information and communication technology in support of health systems’ processes. This is due to the fact that most of health organizations are driven by information and communication technology. The program embodies the features of effective applied health informatics master programs recommended by the International Medical Informatics Association on education in health informatics and delineated as curricula integrating three areas of knowledge and skills: 1) Methodology and technology for the processing of data, information and knowledge in medicine and healthcare, 2) Medicine, health and biosciences, and 3) Informatics/ computer science, mathematics and biometry.Conclusions The health informatics master program (MHI) immerses students in the multidisciplinary field of health informatics education. Graduates of the MHI program will be wellprepared informaticians for leadership positions, able to meet the increasing demands in the field of health informatics to manage, plan, develop, and provide expert consultations to the healthcare sectors.
Keywords: Health Informatics; Health information management Education; Health Information Systems; and Health Studies